Computationally efficient equalization of room impulse responses robust to system estimation errors - Zhang,W; Gaubitch,ND; Naylor,PA (2008)
Equalization techniques for room impulse responses (RIRs) are important in acoustic signal processing applications such as speech dereverberation. In practice, only approximate estimates of the RIRs are available and the inverse filters designed from.....